2011
DOI: 10.1001/archsurg.2011.212
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Resection vs Minimally Invasive Radiofrequency Ablation for the Treatment of Colorectal Liver Metastases

Abstract: Hypothesis: Current literature evaluating radiofrequency ablation (RFA) for treatment of colorectal liver metastases describes high-risk surgical candidates or patients with unresectable disease. This creates bias when comparing RFA and hepatic resection. A Markov analysis would define theoretical outcomes necessary for RFA to demonstrate equivalence to resection.Design: A multistate Markov decision analytic model was constructed. Second-order Monte Carlo analysis was used to simulate a randomized controlled t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 55 publications
0
17
0
Order By: Relevance
“…RF ablation is widely and routinely successfully practiced as an anticancer therapy for both primary and metastatic focal liver tumors (25). However, despite long-standing knowledge of the presence of a "red" inflammatory rim surrounding the ablation zone (5), little is known about the organ environment and cellular responses to the thermal …”
Section: Discussionmentioning
confidence: 99%
“…RF ablation is widely and routinely successfully practiced as an anticancer therapy for both primary and metastatic focal liver tumors (25). However, despite long-standing knowledge of the presence of a "red" inflammatory rim surrounding the ablation zone (5), little is known about the organ environment and cellular responses to the thermal …”
Section: Discussionmentioning
confidence: 99%
“…The question of where ablation fits in the overall management of patients with metastatic colorectal cancer is still being debated. In the last few years there have been numerous reviews of the ablation literature [13][14][15][16][17][18][19][20][21][22][23][24][25][26]. All of these have concluded that there is insufficient data, in particular randomised controlled trial (RCT) data, and as a result have had difficulty providing recommendations on the role of ablation.…”
Section: Introductionmentioning
confidence: 99%
“…This method facilitates thermal injury and thus cell death by means of coagulation necrosis to the tumor through electromagnetic energy deposition and is also used for the treatment of other malignant diseases in the liver, lung, kidney, and bone (9)(10)(11)(12). Beyond serving as a bridge to liver transplantation (13), RF ablation has significantly extended the life expectancy of many patients (14). Furthermore, RF ablation provides additional potential advantages over surgical resection owing to reduced morbidity by ablating a relatively small portion of the liver and can be performed as an outpatient therapy (15).…”
Section: Experimental Studiesmentioning
confidence: 99%